Contact Electroanatomic Mapping Derived Voltage Criteria for Characterizing Left Atrial Scar in Patients Undergoing Ablation for Atrial Fibrillation. (11th June 2014) - KAPA, SURAJ; DESJARDINS, BENOIT; CALLANS, DAVID J.; MARCHLINSKI, FRANCIS E.; DIXIT, SANJAY
Voltage Criteria for Left Atrial Scar Background Criteria have not been established for identifying LA scar using electroanatomic mapping (EAM). It is also unclear if voltage criteria using EAM may assist in identifying areas of pulmonary vein (PV) reconnection in patients undergoing repeat AF ablation. Objectives To characterize left atrial (LA) voltage in patients undergoing atrial fibrillation (AF) ablation. Methods An LA shell was created and bipolar voltage amplitude (in mV) at each point was measured. The shell was divided into 8 regions. Bipolar voltage values lower than the amplitude of 95% of sampled points was used as the upper cutoff value. Delayed enhancement (DE) cardiac magnetic resonance imaging (CMRI) sequences were performed to validate voltage cutoffs. Results Twenty patients participated. A mean of 141 ± 12 points constituted the LA map that was created during sinus rhythm (SR). In patients undergoing initial AF ablation, mean bipolar LA voltage was 1.44 ± 1.27 mV. In patients undergoing repeat AF ablation, scar along the posterior wall and LA–PV junction was identified using a voltage cutoff <0.2 mV, whereas a cutoff <0.45 mV best identified scar at other locations. This voltage range (0.2–0.45 mV) was useful to identify areas of reconnection around the PVs. On DE CMRI, a bipolar voltage cutoff of 0.27 mV performed best for delineating scar (sensitivity: 90%, specificity: 83%). Conclusions In patients undergoing AF ablation, EAM derived LA bipolar voltage shows regional variation. For maps acquired during SR, a voltage range of 0.2–0.45 mV can accurately demarcate LA scar distribution. This can be helpful in identifying PV reconnection in patients undergoing repeat AF ablation.